NYPA PALM SAP AS FEEDSTOCK FOR FERMENTED ALCOHOL PRODUCTION - M Udiharto (Testing Center for Oil and Gas LEMIGAS, 2007)
Nypa palm is the among the few palms that grow well in mangroves. The tapping fromfruit of nypa palm that produces the sap is a good substance for alcohol fermentation dueto its high sugar and low ash contents.The implementation of alcohol fermentation by nypa palm sap was conducted in laboratoryscale. The result shows that the sap of nypa palm is a good feedstock for fermentedalcohol. The best yield is obtained by fermentation of feedstock containing 25% starter,4% NPK solution, and 5% bread yeast. The yield of alcohol concentration is about 11%(88% alcohol content) of feedstock.